2019
DOI: 10.1002/hed.25617
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic swallowing examination for early detection of neopharyngeal fistula after salvage total laryngectomy: A preliminary study

Abstract: Background The current study investigated the feasibility of ultrasonographic swallowing examination (USSE) for the evaluation of neopharynx and early detection of neopharyngeal fistula after salvage total laryngectomy. Methods A prospective case series‐based study involving 16 patients who underwent salvage total laryngectomy was conducted. USSE was performed on postoperative days 5‐7, and oral diet initiation was determined based on the USSE results. Results Fistula of the neopharynx was detected in four pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Immediately after the intervention, additional conditions occur that complicate the physiology of swallowing. The study showed that 27% of total laryngectomized patients experience additional complications after surgical treatment, namely 1) edema of the pharyngeal mucosa, which usually resolves spontaneously within a few months of surgery; 2) fistulas whose incidence varies from 4 to 75% of laryngectomized patients; 3) functional barriers to bolus transit such as stenosis, strictures, obstruction, the presence of pseudoepiglottis or areas of excess tissue "pockets" where food and fluid accumulate, 4) return of nasal contents reported in 9% of patients after laryngectomy and explained is velopharyngeal incompetence; 5) poor motility of the esophagus; 6) reflux; 7) changes in language mobility in the region of the base (26,27).…”
Section: Total Laryngectomymentioning
confidence: 99%
“…Immediately after the intervention, additional conditions occur that complicate the physiology of swallowing. The study showed that 27% of total laryngectomized patients experience additional complications after surgical treatment, namely 1) edema of the pharyngeal mucosa, which usually resolves spontaneously within a few months of surgery; 2) fistulas whose incidence varies from 4 to 75% of laryngectomized patients; 3) functional barriers to bolus transit such as stenosis, strictures, obstruction, the presence of pseudoepiglottis or areas of excess tissue "pockets" where food and fluid accumulate, 4) return of nasal contents reported in 9% of patients after laryngectomy and explained is velopharyngeal incompetence; 5) poor motility of the esophagus; 6) reflux; 7) changes in language mobility in the region of the base (26,27).…”
Section: Total Laryngectomymentioning
confidence: 99%